OZF is a Claspin‐interacting protein essential to maintain the replication fork progression rate under replication stress. Issue 5 (8th April 2020) - Feu, Sonia; Unzueta, Fernando; Llopis, Alba; Semple, Jennifer I.; Ercilla, Amaia; Guaita‐Esteruelas, Sandra; Jaumot, Montserrat; Freire, Raimundo; Agell, Neus
Abstract: DNA replication is essential for cell proliferation and is one of the cell cycle stages where DNA is more vulnerable. Replication stress is a prominent property of tumor cells and an emerging target for cancer therapy. Although it is not directly involved in nucleotide incorporation, Claspin is a protein with relevant functions in DNA replication. It harbors a DNA‐binding domain that interacts preferentially with branched or forked DNA molecules. It also acts as a platform for the interaction of proteins related to DNA damage checkpoint activation, DNA repair, DNA replication origin firing, and fork progression. In order to find new proteins potentially involved in the regulation of DNA replication, we performed a two‐hybrid screen to discover new Claspin‐binding proteins. This system allowed us to identify the zinc‐finger protein OZF (ZNF146) as a new Claspin‐interacting protein. OZF is also present at replication forks and co‐immunoprecipitates not only with Claspin but also with other replisome components. Interestingly, OZF depletion does not affect DNA replication in a normal cell cycle, but its depletion induces a reduction in the fork progression rate under replication stress conditions. Our results suggest that OZF is a Claspin‐binding protein with a specific function in fork progression under replication stress.